The Role of Microbial Aspartic Protease Enzyme in Food and Beverage Industries - Jermen Mamo; Fassil Assefa (Journal of Food Quality)
Proteases represent one of the three largest groups of industrial enzymes and account for about 60% of the total global enzymes sale. According to the Nomenclature Committee of the International Union of Biochemistry and Molecular Biology, proteases are classified in enzymes of class 3, the hydrolases, and the subclass 3.4, the peptide hydrolases or peptidase. Proteases are generally grouped into two main classes based on their site of action, that is, exopeptidases and endopeptidases. Protease has also been grouped into four classes based on their catalytic action: aspartic, cysteine, metallo, and serine proteases. However, lately, three new systems have been defined: the threonine-based proteasome system, the glutamate-glutamine system of eqolisin, and the serine-glutamate-aspartate system of sedolisin. Aspartic proteases (EC 3.4.23) are peptidases that display various activities and specificities. It has two aspartic acid residues (Asp32 and Asp215) within their active site which are useful for their catalytic activity. Most of the aspartic proteases display best enzyme activity at low pH (pH 3 to 4) and have isoelectric points in the pH range of 3 to 4.5. They are inhibited by pepstatin. The failure of the plant and animal proteases to meet the present global enzyme demand has directed to an increasing interest in microbial proteases. Microbial proteases are preferred over plant protease because they have most of the characteristics required for their biotechnological applications. Aspartic proteases are found in molds and yeasts but rarely in bacteria. Aspartic protease enzymes from microbial sources are mainly categorized into two groups: (i) the pepsin-like enzymes produced by Aspergillus, Penicillium, Rhizopus, and Neurospora and (ii) the rennin-like enzymes produced by Endothia and Mucor spp., such as Mucor miehei, M. pusillus, and Endothia parasitica. Aspartic proteases of microbial origin have a wide range of application in food and beverage industries. These include as milk-clotting enzyme for cheese manufacturing, degradation of protein turbidity complex in fruit juices and alcoholic liquors, and modifying wheat gluten in bread by proteolysis.